PERAHU TRADISIONAL SEBAGAI IDENTITAS BUDAYA MARITIM MASYARAKAT AMBON - Charles Pesurnay (Fakultas Ilmu Sosial dan Ilmu Politik, 2025)
This systematic literature review examines the effectiveness and ethical challenges of virtual influencers as brand ambassadors in public relations practice. Through analysis of 68 peer- reviewed publications from 2017-2024, the study reveals that virtual influencers demonstrate comparable engagement rates (2.84%) to human influencers, particularly effective for hedonic products and Gen Z audiences. However, they face significant trustworthiness gaps (M=4.1 vs. 5.2 for humans, p<0.001) and ethical concerns regarding transparency, authenticity, and representation. Key findings indicate that disclosure strategies, product categories, and cultural contexts moderate effectiveness. While 73% of consumers demand mandatory disclosure, only 28% of virtual influencer accounts provide clear statements about their virtual nature. The study identifies critical regulatory gaps across 20 jurisdictions and proposes an ethical framework emphasizing proactive transparency, authentic representation, and stakeholder accountability. Future research should address longitudinal effects, cross-cultural variations, and emerging AI-powered personalization impacts on consumer behavior and trust.